Solvability of n-point problems with parameter for system of differential equation - Sobkovich, R.I.; Kazmerchuk, A.I. (Carpathian Mathematical Publications, 2010)
The n-point problems for non-linear systems of differential equation is investigated. Existence and uniqueness theorems are proved.